2019
DOI: 10.1186/s40560-019-0382-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative capillary refill time predicts sepsis in patients with suspected infection in the emergency department: an observational study

Abstract: Background Outcomes in emergent patients with suspected infection depend on how quickly clinicians evaluate the patients and start treatment. This study was performed to compare the predictive ability of the quantitative capillary refill time (Q-CRT) as a new rapid index versus the quick sequential organ failure assessment (qSOFA) score and the systemic inflammatory response syndrome (SIRS) score for sepsis screening in the emergency department. Methods This was a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…One recent publication detailed a new technology that can obtain capillary refill using a different optic method than traditional transmitted pulse oximetry with improved accuracy, but further clinical trials are needed. 29 In 2019, Yasufumi et al 30 repurposed a pulse oximeter to quantitatively measure CRTs. The subject places their finger inside the device, which exerts pressure to stop blood flow temporarily, then releases and measures the transmitted light utilizing existing pulse oximetry optic sensor technology.…”
Section: Resultsmentioning
confidence: 99%
“…One recent publication detailed a new technology that can obtain capillary refill using a different optic method than traditional transmitted pulse oximetry with improved accuracy, but further clinical trials are needed. 29 In 2019, Yasufumi et al 30 repurposed a pulse oximeter to quantitatively measure CRTs. The subject places their finger inside the device, which exerts pressure to stop blood flow temporarily, then releases and measures the transmitted light utilizing existing pulse oximetry optic sensor technology.…”
Section: Resultsmentioning
confidence: 99%
“…Although it did not reach statistical significance ( p = 0.06), when utilizing a pragmatic Bayesian analysis CRT was superior ( 8 ). A more recent study evaluated objective CRT measurement through a transmitted pulse oximetry light source and were able to show it significantly improved the test characteristics of standard sepsis screening scores in the ED ( 9 ). This type of technology has great promise for ED triage where studies have shown the ability to accurately triage sepsis patients can have significant impact on outcomes ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results suggest that Q-CRT might be an effective measure of insufficient global tissue perfusion and shock in both the ICU and ED. In ED patients with suspected infection, Yasufumi et al ( 38 ) investigated the ability of Q-CRT to predict sepsis compared with quick sequential organ failure assessment (qSOFA) and systemic inflammatory response syndrome (SIRS) scores. The authors reported that the accuracy of Q-CRT in predicting sepsis was comparable to qSOFA scores, SIRS scores, and lactate level.…”
Section: Methods To Monitor Peripheral Perfusionmentioning
confidence: 99%